2020
DOI: 10.1042/bsr20200790
|View full text |Cite
|
Sign up to set email alerts
|

Identification of feature autophagy-related genes in patients with acute myocardial infarction based on bioinformatics analyses

Abstract: Abstract Objective: To identify feature autophagy-related genes (ARGs) in patients with acute myocardial infarction (AMI) and further investigate their value in the diagnosis of AMI. Methods: Gene microarray expression data of AMI peripheral blood samples were downloaded from the GSE66360 dataset. The data were randomly classified into a discovery cohort (21 AMI patients and 22 healthy controls) and a validation cohort (28 AMI pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The FoxO transcription factors are regulated by upstream signaling molecules such as PI3K, AMP-kinase or SIRT genes, and regulate the downstream transcription of proteins such as calcineurin, muscle RING finger1, muscle atrophy F-box, pyruvate dehydrogenase kinase 4 and coactivator-1α [ 16 ]. This has a direct impact on the regulation of protein synthesis, apoptosis and autophagy, finally leading to structural changes of the myocardium, such as MF [ 17 , 18 ]. We found a significantly upregulated expression of both upstream and downstream interaction partners of FoxO molecular effectors in these MF models, confirming the important role of FoxO signaling in the development and progression of MF.…”
Section: Discussionmentioning
confidence: 99%
“…The FoxO transcription factors are regulated by upstream signaling molecules such as PI3K, AMP-kinase or SIRT genes, and regulate the downstream transcription of proteins such as calcineurin, muscle RING finger1, muscle atrophy F-box, pyruvate dehydrogenase kinase 4 and coactivator-1α [ 16 ]. This has a direct impact on the regulation of protein synthesis, apoptosis and autophagy, finally leading to structural changes of the myocardium, such as MF [ 17 , 18 ]. We found a significantly upregulated expression of both upstream and downstream interaction partners of FoxO molecular effectors in these MF models, confirming the important role of FoxO signaling in the development and progression of MF.…”
Section: Discussionmentioning
confidence: 99%
“…ARGs have been shown to be of great value in the diagnosis and/or prognostic evaluation of diseases such as cancer, dilated cardiomyopathy, acute myocardial infarction, diabetic nephropathy, pulmonary hypertension, dermatomyositis, and rheumatoid arthritis ( Du et al, 2020 ; Tong et al, 2021 ; Bai et al, 2022 ; Fan et al, 2022 ; Wang et al, 2022 ; Yang et al, 2022 ; Zhang et al, 2022 ). Therefore, ROC curve and survival analysis were performed on key genes to explore their diagnostic efficacy and prognostic value in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Bo's group identified functional variants of autophagy-related genes, for instance, ATG5 [ 40 ], ATG7 [ 41 ], ATG16L1 [ 42 ], and LC3B [ 43 ] in AMI patients. It has been identified that 7 DEARGs (WDFY3, TP53INP2, GABARAPL1, CDKN1A, DDIT3, NAMPT, and FOS) in AMI based on a feature selection algorithm, known as support vector machine-recursive feature elimination (SVM-RFE), which can be used to diagnose AMI as a potential biological marker [ 44 ]. On the other hand, it has been demonstrated in numerous studies that immune cells play an essential function in the development of AMI and postinfarction cardiac repair and remodeling [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%